New Student Admission System: The Influence of Website Usage on Customer Satisfaction - Puji Puji; Irawati Irawati; Rini Setyaningsih; Arrum Intan Sari; Edi Iskandar (Journal of Islamic Education Students (JIES), 2026)
The digitalization of educational services encourages schools to implement web-based New Student Admission Systems to improve service quality and customer satisfaction. This study aimed to examine the effect of the web-based PSB Online admission system on customer satisfaction at MA Jabal Nur Kandis and to identify implementation challenges. A quantitative correlational design was employed involving 31 tenth-grade students as respondents. Data were collected through questionnaires and documentation and analyzed using percentage analysis and simple regression. The results showed that the implementation level of the web-based admission system reached 74.49%, while customer satisfaction reached 93.87%. The correlation test indicated a positive relationship between the web-based admission system and customer satisfaction (r = 0.428 > 0.355 at the 5% significance level), with a coefficient of determination (R²) of 0.7814, meaning that 78.14% of customer satisfaction was influenced by the system. These findings suggest that better implementation of the web-based admission system leads to higher customer satisfaction. However, the study was limited to a small sample size and a single institution; therefore, future research should involve broader samples and additional relevant variables.